Rare monomorphic epithelial intestinal T-cell lymphoma of the stomach with a giant gastric perforation rescued by liver-covering sutures followed by a total gastrectomy and lateral hepatectomy: a case report - Keiji Muramoto; Sachiko Kaida; Toru Miyake; Rie Nishimura; Katsuyuki Kito; Masanori Shiohara; Ryoji Kushima; Tomoharu Shimizu; Masaji Tani (Surgical Case Reports)
Abstract Background Monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL), a type of peripheral T-cell lymphoma, rarely involves the stomach as the primary organ. Advanced MEITL, for which there is currently no established treatment, causes gastrointestinal perforations and is characterized by a poor response to chemotherapy. Case presentation A 69-year-old man had undergone chemotherapy for MEITL of the whole stomach. He subsequently developed acute abdominal pain, and computed tomography revealed a giant perforation in the anterior gastric wall adjacent to the lateral segment of the liver. The perforation was rescued through closure with liver-covering sutures. Thereafter, a total gastrectomy and a left hepatectomy were performed and he recovered enough to tolerate oral intake. However, despite ongoing chemotherapy, the patient died 83 days after the gastric perforation (10 months after being diagnosed with the lymphoma) owing to rapid progression of the MEITL. Conclusion In the rare case of a giant gastric perforation after chemotherapy for gastric MEITL, rescue is possible through liver-covering sutures followed by a total gastrectomy and lateral hepatectomy.